Enhancing Environmental Awareness in Early Childhood Through the Trash Tracking Game - Halida; Aswat, Bujang; Putri, Ayu Aprilia Pangestu; Dharmayanti, Putu Ari; Jamain, Ririanti Rachmayanie (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
This research is based on observation data and interviews with kindergarten teachers, which revealed a low level of environmental care behaviours among children. The observed behavior includes the children's lack of attention to wet and dry waste scattered around the kindergarten environment. Sensitivity to a clean environment is essential to achieving optimal learning and character development in children. This study aims to improve environmental care behaviours through the Trash Tracking game. The research uses a quantitative approach with an experimental design of one group pretest-post-test. The subjects of the study were 17 children aged 5-6 years, consisting of 8 girls and 9 boys. Data were collected through observation with the same instrument related to environmental care behaviours administered during the pretest and post-test. The data were analyzed using paired t-test. The results showed that the Trash Tracking game, which is engaging and enjoyable, positively influenced the children's behavior toward environmental care. This game also helped children get accustomed to cleaning up waste inside and outside the classroom, as well as distinguishing between wet and dry waste. The children's awareness of preserving a clean environment improved, supporting a conducive and comfortable learning process both inside and outside the classroom.